CURRENTS AND MIXING ON THE SILL OF AMBON BAY MEASURED WITH DROGUES - Walman, -; Anderson, James Jay (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1987)
Currents and mixing properties on the sill of Ambon Bay were measured with drogues. Current speed of 0.62 m/sec was observed. A mixing model suggests material released on the sill would decrease by a factor of 2 x 104 in one hour. Drogue construction and data reduction methods are described.